CONTRIBUTION OF AGRO-ECOSYSTEM IN IMPROVING AGRICULTURAL RESILIENCE AMONG FARMERS IN WHITE NILE SUDAN - Kabbar, Reem Fadul; Alfadul, Esmail; Babiker, Abdelmoneim A. (International Journal of Research -GRANTHAALAYAH, 2020)
This paper was designed to assess contribution of agro-ecosystem after intervention in improving agricultural resilience among farmers in White Nile State of Sudan. The study was based on primary data collected from 200 farmers by a questionnaire. A stratified sampling method was followed to select 200 farmers. Descriptive statistics (frequency and percentage Model of agricultural resilience consisted of two important dependent variables income from agriculture and adaptive capacity of the farmers against the changes in agro-ecosystem. farmers had many practices to adapt with change in agro-ecosystem. The results of analysing the model of agricultural resilience discovered males as more resilient than females. The factors age, years of experience and years of education were found to increase agricultural resilience of the farmers. Moreover, farmers of sesame and peanut were more adaptive to the change in agro-ecosystem than farmers of the sorghum. The study also revealed that farmers benefited significantly from Khor Abu Habil Water. Regarding to the local knowledge of the farmers in the study area there were natural predators helping in defeating insects, the results discovered that negative relationship between the conflicts in the study area and the income from agriculture. The more conflict existing in the area the less income from agriculture will be achieved.